Knock-Down of HOXB8 Prohibits Proliferation and Migration of Colorectal Cancer Cells via Wnt/β-Catenin Signaling Pathway - Li, Xiang (Med Sci Monit, 2019)
BACKGROUND: There has been no research on the mechanism of HOXB8 action on colorectal cancer so far. This study was designed to investigate the mechanism of HOXB8 regulating colorectal cancer cell proliferation and invasion in vivo and in vitro. MATERIAL/METHODS: HOXB8 shRNA, HOXB8 overexpression, and negative control vector were designed and stably transfected into HCT116 cells. MTT assays were performed to detect cell proliferation. Western blot was utilized to detect HOXB8 expression level in HCT116 stable cells. The invasive and migration abilities were detected by Transwell assay and wound-healing assay. RESULTS: HOXB8 knockdown inhibited cell proliferation. The invasiveness of HCT116 cells was significantly reduced following HOXB8 depletion compared with that in the shRNA control group, whereby the rates were reduced by 67% in HOXB8 knockdown group. The wound-healing rate of HOXB8 over-expression cells was significantly increased comparing with that of cells in the blank control group (P<0.05). HOXB8 knockdown promotes apoptosis of HCT116 cells. The expression of E-cadherin was restrained in the HOXB8 over-expression group and increased in the HOXB8 knockdown group. CONCLUSIONS: Knock-down of HOXB8 prohibits the proliferation and migration of colorectal cancer cells via the Wnt/β-catenin signaling pathway and the downregulation of various factors, such as MMP2, c-Myc, CyclinD1,and vimentin. Our data suggested that HOXB8 has great potential to be developed as a novel therapeutic agent for the treatment of human colorectal cancer.